The Relevance of Islamic Values in the Martabat Tujuh Constitution: A Study of the Code of Ethics and Conduct for Civil Servants - Suwandi; Halilul Khairi; M. Nopri Ramadani Utama Buhri; Sharifah Nursyahidah Syed Annuar (IBDA` : Jurnal Kajian Islam dan Budaya, 2024)
This study examines the cultural concepts within the Martabat Tujuh Constitution of the Buton Sultanate in conjunction with Islamic principles and their relevance to government administration. The objective is to assess the relevance of Islamic valuesfor local government administration, particularly the code of ethics and conduct for civil servants. The literature review analyzes the revelant textual sources to identify the Islamic values embedded in the Martabat Tujuh Constitution and their application in governance. The study found that the Islamic values reflected in the Martabat Tujuh Constitution are relevant to the code of ethics and conduct for civil servants in government administration. The implementation of these Islamic values can help prevent corruption and other types of ethical miscoduct in government. By integrating the Islamic values of the Martabat Tujuh Constitution civil servants can implement a well-rounded code of ethics and conduct and support ethical governance